Proust and the squid : the story and science of the reading brain - Wolf, Maryanne (New York : Harper Perennial, 2008)
A developmental psychologist evaluates the ways in which reading and writing have transformed the human brain, in an anecdotal study that reveals the significant changes in evolutionary brain physiology throughout history.
Reading lessons from Proust and the squid -- How the brain adapted itself to read : the first writing systems -- The birth of an alphabet and Socrates' protests -- The beginnings of reading development, or not -- The "natural history" of reading development : connecting the parts of the young reading brain -- The unending story of reading's development -- Dyslexia's puzzle and the brain's design -- Genes, gifts, and dyslexia -- Conclusions : from the reading brain to "what comes next."
Bibliografija: str. [237]-295.
Kazalo
Keywords: Brain -- Evolution; Neurophysiology; Reading comprehension; Reading -- Research; Brain -- growth & development; Brain -- physiology; Comprehension -- physiology; Dyslexia; Reading; Reading; mozak; evolucija; čitanje; disleksija; psihologija; neuropsihologija